Workshop on Small Farmers and Agril. Labour - Planning Commission (Planning Commission, 1970)
As a part of the programme for removing the imbalance in the rural economy as between different areas and different classes of producers and for providing larger employment opportunities particularly the small farmers, marginal farmers and agricultural labour, 45 pilot projects arc proposed to be undertaken for the benefit of potentially viable small farmers and another 40 projects for marginal farmers and agricultural labour with an outlay of Rs. 115 crores. The object of these projects is to increase the income and employment opportunities to the maximum extent possible in agriculture supplemented, where necessary, by ancillary occupations including animal husbandry, cottage industries and productive rural works.
Government of India, Planning Commission
Government of India, Planning Commission